Trafficking of women and girls in the District of Seke: Lessons from the Zimbabwe’s Second Republic - Maybe Zengenene (Faculty of Social and Political Science, Universitas Airlangga, 2020)
The study explores the phenomenon of human trafficking in Zimbabwe’s second republic under President Emerson Mnangagwa. Using conflict theory, the study argues that the discourse of human trafficking in Zimbabwe is a complex phenomenon that has led to women’s and girls’ vulnerability in the Seke District. Primary data gathered from five female core informants who have been the direct victims of human trafficking and three significant others who were the parents and guardians of human trafficking victims. The snowball sampling technique was employed to obtain the female core informants for the in-depth interviews. The study also benefitted from secondary sources such as journal articles, online newspapers, government, and international UN, ILO, UNESCO, and UNICEF reports. The results of this study show that eco-socio and political ills such as a high rate of unemployment, a shortage of essential goods, cash, corruption, electricity, gender inequality, poverty, power relations and the continuous harassment by the security forces such as the police and the army have escalated the vulnerability of women to human trafficking in Zimbabwe. Since Zimbabwe’s eco-political situation is a powerful determinant of both the continuation and abandonment of the human trafficking social phenomena, this study recommends that the present government solve the grassroots causes of the phenomena. With enforcement at the grassroots level and regional and international initiatives, human trafficking can be combated.